MODERN APPROACHES TO THE DEVELOPMENT OF PROFESSIONAL COMPETENCIES OF REHABILITATION SPECIALISTS - Hubenko, I. Ya.; Stepanova, H. M.; Shevchenko, O. T. (Rehabilitation and Recreation, 2025)
The article explores the evolution and current state of implementing the competency-based approach in the professional training of rehabilitation specialists. The study aims to analyze global experience in developing professional competencies of rehabilitation specialists and identify promising directions for improving their training. Based on the analysis of international documents, scientific publications, and educational practices, the transformation of educational paradigms from traditional to competency-based learning models is examined. It has been established that modern training of rehabilitation specialists is based on the principles of evidence-based practice, cultural competence, professional ethics, and interdisciplinary collaboration. Special attention is paid to implementing the concept of entrustable professional activities (EPA) as an innovative approach to assessing specialists’ readiness for independent practice. The study thoroughly examines competency assessment systems, including a five-level scale of readiness for independent practice, which allows for an objective determination of students’ professional training level. The experience of leading countries in implementing the competency-based approach in medical education and rehabilitation, including practices from the USA, Canada, European Union countries, and Australia, has been analyzed. A trend towards international standardization of requirements for rehabilitation specialists’ competencies has been identified, as reflected in the documents of the World Confederation for Physical Therapy and the WHO Rehabilitation Competency Framework. The necessity of practical training in real clinical settings for integrating theoretical knowledge with practical skills has been substantiated. The specifics of implementing the competency-based approach in the Ukrainian system of training rehabilitation specialists, including the peculiarities of forming educational standards and accrediting educational programs, have been examined. The necessity of implementing innovative assessment methods in the educational process and creating a unified system for monitoring students’ professional competencies has been outlined. The prospects for developing a competency-based approach in Ukraine’s rehabilitation education system have been identified, taking into account international standards and modern labor market requirements. The importance of implementing assessment systems that reliably determine graduates’ readiness for independent practice and the need for continuous professional development throughout their careers has been emphasized.